Model Perilaku Pengelolaan Keuangan Berbasis Pengetahuan Keuangan dan Sikap Keuangan pada UMKM di Bumi Raya, Morowali - Anisah, Anisah; D, Salma; Alwi, Miftahul Jannah; Irawati, Iin; Saransi, Ulfa (Fakultas Ekonomi Universitas Samudra, 2025)
The research analyzes the influence of financial knowledge on financial management behavior, by placing financial attitudes as a mediating variable. This quantitative research uses MSMEs operating in the Bumi Raya area, Morowali as the research population, where 73 respondents were selected as samples. Data analysis uses structural equation modeling (SEM), which is operationalized through Partial Least Square (PLS) path analysis using the WarpPLS version 8 program. The results state two important conclusions. First, financial knowledge does not have a significant effect on financial management behavior, but shows a real contribution in forming financial attitudes. Second, financial attitude is proven to have a strategic function as a mediating variable between financial knowledge and financial management behavior among MSMEs operating in the research location, as well as having a substantial positive influence on financial management behavior patterns.